2018
DOI: 10.1038/nprot.2018.036
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorimetric quantification of antibiotic drug concentration in bacterial cells for the characterization of translocation across bacterial membranes

Abstract: The efficacy of antibacterial molecules depends on their capacity to reach inhibitory concentrations in the vicinity of their target. This is particularly challenging for drugs directed against Gram-negative bacteria, which have a complex envelope comprising two membranes and efflux pumps. Precise determination of the bacterial drug content is an essential prerequisite for drug development. Here we describe three approaches that have been developed in our laboratories to quantify drugs accumulated in intact ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 68 publications
0
65
0
Order By: Relevance
“…These compounds differ in their molecular and physicochemical properties while they share a similar core structure (Table 1). Susceptibility assays were performed using isogenic E. coli K12 strains expressing various levels of AcrAB: AG100 (wild type), AG100A (AcrAB-efficient mutant), and AG102 (overexpressing AcrAB) 27 (see "Methods").…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds differ in their molecular and physicochemical properties while they share a similar core structure (Table 1). Susceptibility assays were performed using isogenic E. coli K12 strains expressing various levels of AcrAB: AG100 (wild type), AG100A (AcrAB-efficient mutant), and AG102 (overexpressing AcrAB) 27 (see "Methods").…”
Section: Resultsmentioning
confidence: 99%
“…However, the ability of such compounds to reach effective cytoplasmic concentrations remains a key factor for their antimicrobial activity, a question that has not been properly addressed until now. The Innovative Medicine Initiative programs (www.imi.europa.eu) have supported the development of appropriate methods and concepts to measure translocation and to quantify the intrabacterial concentration of drugs 9,27 . Using fluorimetric assays, we previously showed that the molecular properties of three FQs dictate their capacity to accumulate in E. coli expressing or not the major multidrug efflux transporter AcrB, in complex with the adapter protein AcrA (in the following denoted as AcrAB) 8,27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, unlike previous studies using deep UV illumination to study antibiotic uptake in single 20 cells (11,21), since our excitation wavelength is 365 nm, we can work with standard optics and light sources, rather than needing quartz objectives and cover slips, and deep UV light sources which may not be easily accessible.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms 10 are further complicated by the fact that the expression and activity of porins and efflux pumps vary i) with the microenvironment conditions (8) and ii) within an isogenic population exposed to the same environmental landscape (9). Many existing techniques suffer from the requirement of complex washing steps (3,10), with cells only studied after resuspension in contrived nutrient environments (11,12); the washes also increase the chance of cell lysis and efflux or diffusion of 15 the analyte from the cells, besides affecting cellular physiology. Furthermore, the most commonly used techniques are population level assays which cannot investigate heterogeneity in uptake at the single-cell or at the subcellular level.…”
Section: Introductionmentioning
confidence: 99%